2001
DOI: 10.1021/ma010702o
|View full text |Cite
|
Sign up to set email alerts
|

Radical Copolymerization of 2,4-Disubstituted Enynes with Electron-Accepting Comonomers

Abstract: The radical copolymerization of 2,4-disubstituted enynes (CH 2dC(CH3)-CtC-R: R ) Ph (1a), n-Bu (1b), t-Bu (1c), and (CH3)3Si (1d)) with various electron-accepting comonomers is described. The copolymerization gave corresponding copolymers whose yields were dependent upon the electronic character of the comonomers. The enyne components in the copolymers from 1a and 1d consisted of the specific 1,2-polymerized units, while those from 1b and 1c consisted of both the 1,2-and the 1,4-polymerized units. The copolyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The polymer generated at 90 °C was believed to result from the polymerization of terminal diacetylenic moieties and/or silicon-bound enyne moieties, in agreement with other reports on the polymerization of diacetylene monomers 280−283 and aromatic enynes. 284,285 The so-produced electroactive films exhibited an equivalent surface coverage of TTF exceeding 2.0 × 10 −8 mol cm −2 (Figure 16c). Such a polymerization route involving butadiyne segments is particularly attractive because it provides convenient access to surface-bound electroactive polymers with considerably enhanced chemical and thermal stability, as already demonstrated for gold-grafted polydiacetylenic monolayers.…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…The polymer generated at 90 °C was believed to result from the polymerization of terminal diacetylenic moieties and/or silicon-bound enyne moieties, in agreement with other reports on the polymerization of diacetylene monomers 280−283 and aromatic enynes. 284,285 The so-produced electroactive films exhibited an equivalent surface coverage of TTF exceeding 2.0 × 10 −8 mol cm −2 (Figure 16c). Such a polymerization route involving butadiyne segments is particularly attractive because it provides convenient access to surface-bound electroactive polymers with considerably enhanced chemical and thermal stability, as already demonstrated for gold-grafted polydiacetylenic monolayers.…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…In the latter case, the generated polymer is believed to result from the polymerization of terminal diacetylenic moieties and/or silicon-bound enyne moieties, in agreement with previous studies on the polymerization of diacetylene monomers 36−43 and aromatic enynes. 44,45 It has been demonstrated that the polymer materials derived from tailor-made diacetylene derivatives showed interesting optical, spectral, and electronic properties (e.g., stress-induced colorimetric and fluorogenic transitions, sensing capabilities). 37 Moreover, a large palette of structurally organized architectures, such as supramolecular assemblies and ordered nanostructures, could be generated from these functional units.…”
Section: Introductionmentioning
confidence: 99%
“…The controlled polymerization of highly unsaturated monomers plays an important role in the synthesis of well‐defined polymers with unsaturated moieties that are applicable as functional and reactive polymers. For this reason, many efforts have been made to develop precisely controlled polymerizations of, for instance, conjugated dienes,1, 2 allenes,3–5 acetylenes,6–8 and conjugated enynes 9–13. Among them, conjugated enynes are attractive monomers because the controlled polymerization of enynes is expected to give polymers with acetylene, allene, and diene moieties.…”
Section: Introductionmentioning
confidence: 99%